A New Species of Gymnophallid (Digenea) and an Amended Diagnosis of the Genus Gymnophalloides Fujita, 1925 - Cremonte, Florencia; Pina, Susana; Gilardoni, Carmen Mariangel; Rodrigues, Pedro; Chai, Jong-Yil; Ituarte, Cristian Federico (Journal of Parasitology)
Morphological and molecular evidence suggest that specimens formerly described as Lacunovermis sp. from Nacella (Patinigera) spp. (Patellogastropoda: Patellidae) belong to a new species of Gymnophalloides Fujita, 1925. Based on the new information, they are identified as Gymnophalloides nacellae n. sp. The new species differs from Gymnophalloides tokiensis, Gymnophalloides seoi, and Gymnophalloides heardi mainly through the presence of a group of papillae located on the ventral surface between oral and ventral suckers. A detailed morphological study revealed the lack of pars prostatica, a character previously reported in G. seoi, which is why it was formerly placed in the Gymnophallinae. Molecular information proved that G. nacellae is close to G. seoi, being nestled together with Parvatrema representatives. This molecular information, along with the absence of pars prostatica, allows these 2 genera to be placed in Parvatrematinae. An amended diagnosis of Gymnophalloides is provided. Histological sections of mantle epithelium of the limpet show metacercariae attached by their oral and ventral suckers in a similar manner to G. seoi in its host, the oyster Crassostrea gigas. Tissue reaction includes cells of outer mantle epithelium being stretched by sucker attachment, hemocyte infiltration of connective tissue between mantle epitheliums, and abnormal calcareous deposition on the inner surface of the shell. Fil: Cremonte, Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Pina, Susana. Universidad de Porto; Portugal Fil: Gilardoni, Carmen Mariangel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Rodrigues, Pedro. Universidad de Porto; Portugal Fil: Chai, Jong-Yil. Seoul National University; Corea del Sur. Seoul National University Medical Research Center; Corea del Sur Fil: Ituarte, Cristian Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación ...